Pengaruh Likuiditas Dan Ukuran Perusahaan Terhadap Struktur Modal Pada Perusahaan Yang Terdaftar Pada Bursa Efek Indonesia Tahun 2019-2023 - Sulartopo Sulartopo; Sri Yulianingsih; Susilo Adi; Rachmat Setyawan; Robby Andika Kusumajaya (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
Differences in previous research regarding the influence of liquidity and company size on a company's capital structure. The focus of this research is to examine and analyze how liquidity affects the capital structure of a company. Apart from that, it will also be analyzed how company size affects the capital structure of the same company. This research focuses on testing and analyzing how liquidity and the size of a company affect the structure of a company's capital. A technique where multiple linear regression is used to process data using this technique to estimate the value of the dependent variable using multiples of the independent variables. Liquidity has a positive and significant influence on the structure of a company's capital. 2. The size of a company has a positive and significant influence on the structure of a company's capital.